Repair of an aorto-right ventricular tunnel in a newborn - Ziesenitz, Victoria C.; Gorenflo, Matthias; Loukanov, Tsvetomir (Cardiology in the young, 2015)
A newborn presented with an aorto-right ventricular tunnel, a defect connecting the left aortic sinus to the right ventricle. The patient underwent repair on 4th day of life.
Gesehen am 22.09.2020